MALDI-TOF mass spectrometric protein profiling of THP-1 cells and their microvesicles - A. V. Korenevsky (SPb RAACI, 2021)
Extracellular vesicles that are shed from the plasma membranes take an active part in intercellular communication, transporting a wide range of molecules, including proteins, lipids, nucleic acids and carbohydrates, being of great functional importance. One of the steps to better understanding of distant communications of cells and their regulatory mechanisms is a proteomic study of various extracellular vesicles, including microvesicles and exosomes. Pro-inflammatory cytokines produced by monocytes and individual complement system components play a key role in their specific functioning. The aim of this work was to study proteomic composition of THP-1 monocyte-like cells and their microvesicles. The MALDI-mass spectrometric analysis of electrophoretic protein fractions of cell lysates and microvesicles allowed for identifying 107 proteins that perform various functions. Among 19 determined functional groups, the largest ones comprise transcription regulators and proteins with unknown functions. The smallest functional groups include regulators of cell differentiation and development, proteins participating in immune response and inflammation, cellular receptors and their regulators, transporter and transport regulatory proteins, as well as cell proteins mediating adhesion and matrix structures, processing regulators, proteins of ubiquitin-proteasome system, intracellular signaling, autophagy and exocytosis regulators, chromatin structural proteins, hemostatic regulators, and peptide hormones. An intermediate position is occupied by cytokines and growth factors, enzymes, cytoskeleton and motor proteins, as well as RNA processing and translation regulators. The subsequent DAVID Functional Annotation Clustering analysis allowed for identifying the most common groups distributed by their molecular function, biological processes, and cellular component. Separately, in the microvesicles derived from THP-1 monocyte-like cells, proteins of the immune response and inflammation, cytokines and growth factors, intracellular signaling proteins, cell differentiation regulators and developmental proteins, as well as cell adhesion and matrix proteins were identified among other protein molecules. The data obtained on the partial proteome of THP-1 monocyte-like cells and their microvesicles extend the existing knowledge on distant communications between the cells and suggest new mechanisms of interaction between monocytes/macrophages and their microenvironment.